Formaldehyde Molecules Adsorption on Zn Doped Monolayer MoS2: A First-Principles Calculation - Li, Huili; Fu, Ling; He, Chaozheng; Huo, Jinrong; Yang, Houyong; Xie, Tingyue; Zhao, Guozheng; Dong, Guohui (Frontiers in Chemistry, 2021)
Based on the first principles of density functional theory, the adsorption behavior of H2CO on original monolayer MoS2 and Zn doped monolayer MoS2 was studied. The results show that the adsorption of H2CO on the original monolayer MoS2 is very weak, and the electronic structure of the substrate changes little after adsorption. A new kind of surface single cluster catalyst (SCC) was formed after Zn doped monolayer MoS2, where the ZnMo3 small clusters made the surface have high selectivity. The adsorption behavior of H2CO on Zn doped monolayer MoS2 can be divided into two situations. When the H-end of H2CO molecule in the adsorption structure is downward, the adsorption energy is only 0.11 and 0.15 eV and the electronic structure of adsorbed substrate changes smaller. When the O-end of H2CO molecule is downward, the interaction between H2CO and the doped MoS2 is strong leading to the chemical adsorption with the adsorption energy of 0.80 and 0.98 eV. For the O-end-down structure, the adsorption obviously introduces new impurity states into the band gap or results in the redistribution of the original impurity states. All of these may lead to the change of the chemical properties of the doped MoS2 monolayer, which can be used to detect the adsorbed H2CO molecules. The results show that the introduction of appropriate dopant may be a feasible method to improve the performance of MoS2 gas sensor.